Model Pendidikan Formal di Lingkungan Pesantren: Studi di SMK Syubbanul Wathon Magelang - Aulia Fitriani; Sanusi Sanusi; Savina Larasati; Atika Apreliyani; Shela Arie Mutia (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2023)
Islamic boarding school-based schools are one of the educational models that has experienced quite significant development in Indonesia. This model school typology has become one of the educational models that has attracted the attention of some Indonesians. This reason makes sense because the curriculum offered tends to be relatively more comprehensive than if you only study at school or only study at an Islamic boarding school. Islamic boarding school Islamic boarding school is an education provider with a unique concept that combines the Islamic boarding school concept and the school concept as a unified curriculum system. In its management, this institution integrates the Islamic boarding school curriculum into formal education. This research uses observation and interview methods, and is accompanied by literature study methods. The observation method is direct observation of the research object. The interview method is asking questions to dig up information from sources who are the object of research. And the literature study method, where researchers use various literature to obtain research data. This article is very important to read, because it can broaden the reader's insight and this article is different from other articles because it contains about the advantages of formal schools found in Islamic boarding schools. In this article, readers will learn about the integration of the formal education curriculum with the Islamic boarding school curriculum in formal schools under the supervision of Islamic boarding school foundations in the Magelang area.Keywords: Typology, Formal Education, Islamic Boarding School.